2019
DOI: 10.1002/cne.24777
|View full text |Cite
|
Sign up to set email alerts
|

The habenula as an evolutionary conserved link between basal ganglia, limbic, and sensory systems—A phylogenetic comparison based on anuran amphibians

Abstract: Based on anatomical and functional data, the habenula—a phylogenetically old brain structure present in all vertebrates—takes part in the integration of limbic, sensory, and basal ganglia information to guide effective response strategies appropriate to environmental conditions. In the present study, we investigated the connections of the habenular nuclei of the oriental fire‐bellied toad, Bombina orientalis, and compared them with published data from lampreys, chondrichthyes, teleosts, reptiles, birds, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 155 publications
(314 reference statements)
0
15
0
Order By: Relevance
“…In a previous study, we identified prominent projections from the dorsal and ventral habenula to the posterior tubercle, mesencephalic tegmentum, and raphe nuclei in Bombina orientalis (Freudenmacher et al, ). But direct habenula projections to dopaminergic, serotonergic, and histaminergic neurons were not identified.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In a previous study, we identified prominent projections from the dorsal and ventral habenula to the posterior tubercle, mesencephalic tegmentum, and raphe nuclei in Bombina orientalis (Freudenmacher et al, ). But direct habenula projections to dopaminergic, serotonergic, and histaminergic neurons were not identified.…”
Section: Discussionmentioning
confidence: 86%
“…This appears to be mediated by GABAergic neurons in the rostromedial tegmental nucleus (RMTg) and opposes the reward and motor‐activating functions of dopaminergic midbrain neurons (Jhou, Geisler, Marinelli, Degarmo, & Zahm, ). While a structure homologous to the RMTg—located in the dorsal mamillary area—was identified in lampreys (Stephenson‐Jones et al, ), we could identify the superficial mamillary area as a putative RMTg homolog in anuran amphibians (Freudenmacher et al, ). In order to address the question whether the MHb/LHb–(RMTg)–VTA/SNc/raphe circuitry is as well present in anuran amphibians, this study investigated these regions and their topographic and immunohistochemical organization in more detail.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations